Sculpting Success: A Blueprint For 21st-Century Accounting Education Through Innovative Lesson Planning In Vocational High Schools - Suyatmini; Sari, Dhany Efita; Yuningsih, Yuni (Universitas Muhammadiyah Surakarta, 2023)
The Double-Loop Spatial Learning model presents a form of integration with various educational materials, particularly in the context of inland waters within the dynamics of the hydrosphere. This research aims to ascertain the impact of the gamification-assisted double-loop spatial learning model on the critical thinking abilities and environmental decision-making in the study of inland water dynamics pertaining to hydrospheric material, employing a quasi experimental research type with a non-equivalent control group design for the research design. The sampling technique used was purposive sampling, resulting in the selection of students from the 10th grade Social Science 1 class as the experimental group and the 10th grade Social Science 2 class as the control group. Based on the results of the independent sample t-test, it is indicated that there is a significant effect of the gamification-assisted DoubleLoop Spatial Learning model on the critical thinking abilities and environmental decision-making in the experimental group's study of inland waters, with the ttest values obtained being 10.938 for critical thinking ability and 3.522 for environmental decision making.